Christian Colonisation of the Urban Space of Sagunt, Valencian Country (1238–1350) - Mateu, Alexandre (Medieval Settlement Research, 2023)
This study addresses the process of appropriation of urban space by Christians in the Kingdom of Valencia, after the conquest by King James I in 1238. Using Sagunt as a case study, our aim is to examine what the medina, i.e. the older part of the town, was like during the era of Muslim rule (the ‘Andalusi’ period); and how it changed after the expulsion of its Muslim inhabitants in 1248. By utilising extant urban morphology and historical maps, alongside documents and archaeological reports, we can demonstrate the complete transformation of residential areas following Christian colonisation. During this process, the Andalusi street network was modified but never entirely transformed, retaining much of its historical character. The nature of these urban changes leads us to propose the crucial importance of the Christian settlers and the small- to medium-scale building operations they carried out as the principal subject of study when conducting this type of analysis.